Edukasi dan Pelatihan Pembuatan Obat Herbal Antikolesterol Pada Masyarakat Risiko Tinggi di Desa Banjarsari - Fauziah Fauziah; Supriani Supriani; Khamdiyah Indan K; Peppy Octaviani DM; Zahra A. Ristiana (LPPM STIKes Muhammadiyah Ciamis, 2026)
Introduction: Hypercholesterolemia is a prevalent public health problem and a major risk factor for cardiovascular diseases. Because its symptoms are often non-specific, many individuals remain unaware of their condition, highlighting the importance of promotive and preventive strategies to improve community awareness. The use of locally available herbal plants offers a practical approach aligned with traditional knowledge to support cholesterol control. Objective: This community service activity aimed to improve community knowledge and practical skills regarding hypercholesterolemia prevention and the utilization of bay leaves (Syzygium polyanthum) and red ginger (Zingiber officinale var. rubrum) as herbal ingredients for cholesterol management. Method: The program involved community members and was conducted through two main stages: education and training. Educational activities were delivered through interactive lectures supported by leaflets, PowerPoint presentations, and discussion sessions. The training stage provided hands-on practice in preparing herbal beverages using bay leaves and red ginger. Program evaluation was carried out using a questionnaire consisting of 10 true-or-false questions to assess participants’ level of understanding before and after the intervention. Result: The results indicated an improvement in participants’ knowledge and awareness related to hypercholesterolemia and the benefits of herbal plants. Participants demonstrated active engagement during the sessions and showed increased confidence in independently preparing herbal drinks as part of daily preventive practices. Conclusion: Community-based education combined with practical herbal training is an effective promotive and preventive strategy to enhance awareness of hypercholesterolemia and encourage sustainable utilization of local herbal resources.